Examination of Homicides in Houston, Texas, 1985-1994 - Titterington, Victoria ([Verlag nicht ermittelbar], 2002)
As a contribution to nationwide efforts to more thoroughly understand urban violence, this study was conducted to assess the impact of cultural dynamics on homicide rates in Houston, Texas, and to profile homicides in the city from 1985 to 1994. This data collection provides the results of quantitative analysis of data collected from all Houston homicide cases recorded in the police murder logs for 1985-1994. Variables describe the homicide circumstances, the victim-offender relationship, the type of weapon used, and any drug- or gang-related activity involved. Other variables include the year and month in which the homicide occurred, whether the homicide occurred on a weekday or over the weekend, the motive of the homicide, whether the homicide was drug-related, whether the case was cleared by police at time of data entry, weapon type and means of killing, the relationship between the victim and the offender, whether a firearm was the homicide method, whether it was a multiple victim incident or multiple offender incident, whether the victim or the offender was younger than age 15, and the inter-racial relationship between the victim and the offender. Demographic variables include age, sex, and race of the victim as well as the offender.